An Epilepsy-Associated CILK1 Variant Compromises KATNIP Regulation and Impairs Primary Cilia and Hedgehog Signaling - Ana Limerick; Ellie A. McCabe; Jacob S. Turner; Kevin W. Kuang; David L. Brautigan; Yi Hao; Cheuk Ying Chu; Sean H. Fu; Sean Ahmadi; Wenhao Xu; Zheng Fu (Cells, 2024)
Mutations in human CILK1 (ciliogenesis associated kinase 1) are linked to ciliopathies and epilepsy. Homozygous point and nonsense mutations that extinguish kinase activity impair primary cilia function, whereas mutations outside the kinase domain are not well understood. Here, we produced a knock-in mouse equivalent to the human CILK1 A615T variant identified in juvenile myoclonic epilepsy (JME). This residue is in the intrinsically disordered C-terminal region of CILK1 separate from the kinase domain. Mouse embryo fibroblasts (MEFs) with either heterozygous or homozygous A612T mutant alleles exhibited a higher ciliation rate, shorter individual cilia, and upregulation of ciliary Hedgehog signaling. Thus, a single A612T mutant allele was sufficient to impair primary cilia and ciliary signaling in MEFs. Gene expression profiles of wild-type versus mutant MEFs revealed profound changes in cilia-related molecular functions and biological processes. The CILK1 A615T mutant protein was not increased to the same level as the wild-type protein when co-expressed with scaffold protein KATNIP (katanin-interacting protein). Our data show that KATNIP regulation of a JME-associated single-residue variant of CILK1 is compromised, and this impairs the maintenance of primary cilia and Hedgehog signaling.